1992
DOI: 10.1042/bj2820715
|View full text |Cite
|
Sign up to set email alerts
|

Conformational differences between surface-bound and fluid-phase complement-component-C3 fragments. Epitope mapping by cDNA expression

Abstract: In previous studies a subset of complement-component-C3 (C3) epitopes, C3(D), expressed in denatured and surface-bound C3 and C3 fragments, has been described. These epitopes were detected by antibodies raised against denatured C3. In the present study we used a cDNA expression strategy to localize epitopes recognized by monoclonal and polyclonal anti-C3(D) antibodies. First, DNAse I digestion of C3 cDNA was used to generate 200-300 bp fragments. These cDNA fragments were expressed as beta-galactosidase-C3 fus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1993
1993
2005
2005

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Similarly, differential expression of various epitopes on fluid-phase vs surface-bound C3 has already been proposed. Nilsson and coworkers have found that the reactivity of several mAbs recognizing the C3 ␣-chain differ when the C3 fragments are in fluid phase or surface-bound (60).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, differential expression of various epitopes on fluid-phase vs surface-bound C3 has already been proposed. Nilsson and coworkers have found that the reactivity of several mAbs recognizing the C3 ␣-chain differ when the C3 fragments are in fluid phase or surface-bound (60).…”
Section: Discussionmentioning
confidence: 99%
“…The following Ab were used: mouse anti-CD46 mAb MCI20.6 directed against CCP I [21,22] and GB24 directed against CCP III-IV [15], mAb anti-C3b, iC3b and C3c WM1 (European Collection of Animal Cell Cultures, no. 92021211) and 7D326 [23], mAb anti-iC3b and C3dg 7D26 [23], polyclonal rabbit anti-C3b, iC3b and C3c (L440 M. Fontaine, unpublished) and polyclonal goat anti-human C5 (Quidel, San Diego, CA). PE-labeled anti-mouse IgG(H+L) and antigoat Ig(H+L) were purchased from Immunotech (Marseille, France) and Quidel, respectively.…”
Section: Cells Serum and Abmentioning
confidence: 99%
“…7D6I5.1 and 7D33I.1 (against neoepitopes expressed in C3d, in the 20-kD and 40-kD fragments of C3c. respectively) [24]. 7D323.1 (against a neocpitope in C3g) [25] and 7DI69.7 (against epitopes in the /^-chain of C3) [20].…”
Section: Western Blot Analysismentioning
confidence: 99%